2013
DOI: 10.1063/1.4823988
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of hollow BaTiO3 nanofibers and intense visible photoluminescence

Abstract: BaTiO3 hollow nanofibers were fabricated by electrospinning and then subsequent calcination of as-spun nanofibers with a heating rate of 2.5 °C/min. Scanning electron microscope and transmission electron microscope (TEM) results indicated that the heating rate had a significant effect on the morphology of the BaTiO3 hollow nanofibers. The X-ray diffraction, Raman spectroscopy, and TEM results indicate the prepared BaTiO3 hollow nanofibers have tetragonal phases. From the results of the X-ray photoelectron spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Peaks at 778 eV and 793.3 eV, respectively corresponding to the Ba 3d 5/2 and Ba 3d 3/2 , are assigned to the perovskite structure of BaTiO 3 . It is worth pointing out that the higher shoulders at 779.4 eV and 794.6 eV are usually associated with Ba vacancy point defects33. Note that the peak intensity at both 779.4 eV and 794.6 eV increases with the increase in Nd concentration, suggesting that Ba vacancy would boost with the introduction of Nd ions.…”
Section: Resultsmentioning
confidence: 95%
“…Peaks at 778 eV and 793.3 eV, respectively corresponding to the Ba 3d 5/2 and Ba 3d 3/2 , are assigned to the perovskite structure of BaTiO 3 . It is worth pointing out that the higher shoulders at 779.4 eV and 794.6 eV are usually associated with Ba vacancy point defects33. Note that the peak intensity at both 779.4 eV and 794.6 eV increases with the increase in Nd concentration, suggesting that Ba vacancy would boost with the introduction of Nd ions.…”
Section: Resultsmentioning
confidence: 95%
“…From the HRTEM images also clear that even at nanoparticle boundaries the particles is having clear lattice planes without any amorphous nature. In most of the chemical synthesis processes the crystallization temperature for BaTiO 3 is in the range of 600 o C-700 o C. 28,[37][38][39][40] Basically the higher temperatures are used for grain growth and densification in the sintering process.…”
Section: A Discussion On Structural Studiesmentioning
confidence: 99%
“…The data plot for Ba 3d in the pure BaTiO 3 powder (Figure a) reveals its existence in two ferroelectric domains (F 1 and F 2 ) with characteristic binding energy peaks at ∼777.9 eV and ∼779.6 eV for 3d 5/2 . These ferroelectric domains describe the anomalous behavior of Ba 2+ and O 2– coordination (ranging from 12-fold in the bulk to <12-fold near the surface) in the layers of BaTiO 3 crystal during its synthesis. , The F 1 Ba ions in the bulk possess 12-fold oxygen coordination and are positioned at lower binding energy than the F 2 Ba ions lying near the surface with less oxygen coordination. Meanwhile, the Ba ions in BaCO 3 (a precursor in BaTiO 3 synthesis) possess 9-fold oxygen coordination at the same binding energy as with the F 2 domain Ba ions, hence, the binding energy at ∼779.6 eV could result from an overlap between the Ba ions in the F 2 domain and the adsorbed C–O species. , Previous studies have also shown that abrasive (grinding) and/or annealing processes could produce very reactive Ba ions near the surface of BaTiO 3 . This may be the case in the observed spectra of the as-milled and dehydrogenated samples as shown in Figure b.…”
Section: Results and Discussionmentioning
confidence: 96%